2015
DOI: 10.1007/s10439-015-1510-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dynamic Culture and Periodic Compression on Human Mesenchymal Stem Cell Proliferation and Chondrogenesis

Abstract: We have recently developed a bioreactor that can apply both shear and compressive forces to engineered tissues in dynamic culture. In our system, alginate hydrogel beads with encapsulated human mesenchymal stem cells (hMSCs) were cultured under different dynamic conditions while subjected to periodic, compressive force. A customized pressure sensor was developed to track the pressure fluctuations when shear forces and compressive forces were applied. Compared to static culture, dynamic culture can maintain a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 36 publications
1
51
0
Order By: Relevance
“…Pazzano et al () also showed that the flow perfusion was able to maintain the pH gradient throughout the scaffold leading to increased DNA content. However, other researchers found that the flow perfusion led to downregulation of SOX9, GAG, and collagen II expressions, indicating reduced chondrogenic and increased osteogenic differentiation (Guo et al, ; Kock, Malda, Dhert, Ito, & Gawlitta, ; Mizuno, Allemann, & Glowacki, ). The discrepancy can be caused by the higher flow rate used in those studies (0.33, 1, and1.22 ml/min), which led to increased FSS on the cells.…”
Section: Resultsmentioning
confidence: 97%
“…Pazzano et al () also showed that the flow perfusion was able to maintain the pH gradient throughout the scaffold leading to increased DNA content. However, other researchers found that the flow perfusion led to downregulation of SOX9, GAG, and collagen II expressions, indicating reduced chondrogenic and increased osteogenic differentiation (Guo et al, ; Kock, Malda, Dhert, Ito, & Gawlitta, ; Mizuno, Allemann, & Glowacki, ). The discrepancy can be caused by the higher flow rate used in those studies (0.33, 1, and1.22 ml/min), which led to increased FSS on the cells.…”
Section: Resultsmentioning
confidence: 97%
“…One study found hBMSCs encapsulated in alginate beads had 1.6 times more cells [49]. Others found hBMSCs secrete more GAGs in the dynamic environment of a TPB as evidenced by Alcian blue staining [51]. These advantages are likely due to the enhancement in mass transfer caused by perfusion through and around packed scaffolds, which also enhances shear stress.…”
Section: Tubular Perfusion Bioreactormentioning
confidence: 99%
“…Indeed, physical stimuli have been shown to modulate stem cell differentiation. For instance, electrical stimuli in case of cells directed to the nervous, cardiac and muscular systems, or compression and extension in cells aimed to bioengineer tendons and bones [2226]. …”
Section: Reviewmentioning
confidence: 99%